Model Evaluasi Pembelajaran Pendidikan Agama Islam dalam Kurikulum Merdeka - Ali Masngud; Nurfuadi; Muflih Nurriza Pahlawi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Subjects​ Islamic religious education has fundamental role​ as Foundation religious knowledge for participant Muslim education in schools. Implementation learning can obtain results more optimal if using the right evaluation model, as well as in learning Islamic religious education in it contained material about religiousness. Interesting for look at the evaluation model what only one can used in frame do evaluation learning Islamic religious education in curriculum independent as system current curriculum​ this used in Indonesia. Study this use type study descriptive qualitative that is procedure research results​ in the form of descriptive data in the form of words. Collected data originate from references that have linkages with theme study this. Results study this is CIPP evaluation contains four aspect that is context, input, process, and results can guided as an internal model do evaluation learning Islamic religious education on curriculum independent. Evaluation context to learning Islamic religious education was obtained from analysis to curriculum independence will be applied. Evaluation input or input useful in determine planning, strategy, and goals achieved​ as well as alternative taking decision when happen constraint in implementation learning Islamic education. Focused process evaluation on learning process activities Islamic religious education through analysis on curriculum independent. Evaluation product this obtained from analysis to results obtained​ in application learning Islamic religious education on curriculum independent.